MODEL “PIN SENJA” (PUSAT INFORMASI DAN KONSELING REMAJA) SEBAGAI UPAYA PENINGKATAN KESEHATAN REPRODUKSI REMAJA - Dian Isti Angraini; Efrida Warganegara; Ety Apriliana; Novita Carolia; Merry Indah Sari; Efriyan Imantika (JURNAL KEDOKTERAN DAN KESEHATAN, 2022)
The PIN SENJA model (youth information and counseling center) is a model designed and modified for adolescent reproductive health and CIE activities, training on how to maintain the cleanliness and health of adolescent genital and reproductive organs and forming a PIN SENJA ambassador. This model is also designed in order to prepare family life for adolescents who are managed from, by and for adolescents in order to provide information and counseling services on reproductive health, how to protect and prevent reproductive health problems such as premarital sex, teenage pregnancy, early marriage, and genital infection. and sexually transmitted infections, HIV-AIDS, psychotropic narcotics and other addictive substances (drugs) and pornography. The aim of this program is to increase knowledge, attitudes and behavior of adolescents regarding reproductive health, improve adolescent skills to maintain personal hygiene and forming PIN SENJA ambassadors. The method that will be carried out is by providing counseling, training skills, and forming PIN SENJA ambassadors as CIE agents to 40 MA Dinniyah Putri Lampung students. The results of the evaluation of the implementation of community service showed that there was an increase in the participants' understanding by 90% which became a good understanding, and 10% of participants had sufficient understanding of reproductive health for adolescents. The CIE ability of MA Dinniyah Putri Lampung as a participant is also quite good, almost 95% of participants already understand and are able to do CIE through simulation evaluation and discussion. The mean pretest result was 57.87 and an increase in post-test results was 84. Based on the analysis using the Wilcoxon test, it was found that there was a statistically significant difference between the pretest and posttest scores of the participants regarding reproductive health (p = 0.000). Improving the ability of MA Dinniyah Putri Lampung students to conduct CIE on adolescent reproductive health in an effort to prevent adolescent health problems with the PIN SENJA model has proven effective.